2010
DOI: 10.1585/pfr.5.029
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Oscillations Observed in Non-Neutral Electron Plasmas Confined in a Magnetic Field Gradient

Abstract: Non-neutral electron plasmas were confined in an axisymmetric magnetic mirror field of the mirror ratio R ∼ 3. Axial plasma oscillations (Trivelpiece-Gould modes), diocotron oscillations with the azimuthal mode number m = 2, and solitary waves were investigated experimentally. It was observed that the velocities of an electron soliton and an electron hole decreased at high field side in a magnetic mirror confinement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The error becomes larger at the higher field, because the pulse shape becomes broader at the higher field. In previous experiments, 21) it was found that the solitary waves excited in a magnetic field gradient have a higher velocity at the lower field. Although a similar behavior is observed in the current experiment, the details should be checked carefully for the current device.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…The error becomes larger at the higher field, because the pulse shape becomes broader at the higher field. In previous experiments, 21) it was found that the solitary waves excited in a magnetic field gradient have a higher velocity at the lower field. Although a similar behavior is observed in the current experiment, the details should be checked carefully for the current device.…”
mentioning
confidence: 88%
“…The azimuthally segmented electrodes can be used to apply rotating electric fields and to detect azimuthal plasma oscillations. As mentioned in previous papers, [19][20][21] the multiring electrode configuration is quite flexible to apply various electric fields. Two examples of calculated electric potentials along the axis of symmetry are shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of multi-ring electrode structure makes it possible to excite and detect various plasma oscillations and to provide various electric potentials. [28][29][30][31][32] An electron gun at the one end of the trap is set on the axis of symmetry and a Faraday cup is placed at the other end of the trap. The vacuum pressure is ∼5 × 10 −9 torr.…”
mentioning
confidence: 99%